A fixed point theorem in Menger space - Pant, BD; Chauhan, Sunny (Kathmandu University Journal of Science Engineering and Technology, 2011)
The purpose of this paper is to introduce the concept of weakly compatible maps in Menger space and prove a common fixed point theorem in this space. 2010 Mathematics Subject Classification: 54H25.